Meningkatkan Keterampilan Berpikir Kreatif Siswa pada Muatan IPA Menggunakan Model Pembelajaran BARITO di Kelas V SDN 3 Landasan Ulin Barat - Niken Larasati; Aslamiah (CV. ITTC INDONESIA, 2023)
Obstacles in research is the low creative thinking skills of students. The solution to this problem is by applying the BARITO learning model (Problem Based Learning, Team Assisted Individualization and Course Review Horay). This type of research is Classroom Action Research (CAR) and uses a qualitative approach with the subjects of this research being fifth grade students at SDN 3 Landasan Ulin Barat for the academic year 2022/2023 as many as 27 people. Data collection techniques using crosstable in the form of tables and graphs. Data were analyzed using descriptive analysis techniques which were described in the form of scores in tables and graphs which were then interpreted using criteria. The findings show that students' creative thinking skills at meeting 3 get a percentage of 85% of the criteria